2020
DOI: 10.1186/s43042-020-00098-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukins 12B and 17A genetic variation in house dust mites allergy

Abstract: Background The house dust mites (HDM) constitute a major cause of allergic diseases all over the world. Genes encoding interleukins 12B and 17A which determine the course of T cell-mediated immune response are prime candidates as allergic disease susceptibility. The purpose of this study was to evaluate whether a single-nucleotide polymorphisms (SNP) of interleukins 12B + 1188A/C (rs3212227) and 17A −197G/A (rs2275913) confers susceptibility to HDM allergic diseases. Through a case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…This goes in line with other studies that found no evidence of polymorphism effect on cytokine expression. 30,31 On the contrary, other authors reported a significant effect of this SNP on the serum levels of IL-17. A study by Xie et al, 2019, observed decreased IL-17 levels in A-allele carriers of IL-17 rs2275913.…”
Section: Discussionmentioning
confidence: 72%
“…This goes in line with other studies that found no evidence of polymorphism effect on cytokine expression. 30,31 On the contrary, other authors reported a significant effect of this SNP on the serum levels of IL-17. A study by Xie et al, 2019, observed decreased IL-17 levels in A-allele carriers of IL-17 rs2275913.…”
Section: Discussionmentioning
confidence: 72%